2017
DOI: 10.1016/j.jenvman.2016.11.062
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in mapping forest carbon in urban ecosystems

Abstract: Spatially explicit urban forest carbon estimation provides a baseline map for understanding the variation in forest vertical structure, informing sustainable forest management and urban planning. While high-resolution remote sensing has proven promising for carbon mapping in highly fragmented urban landscapes, data cost and availability are the major obstacle prohibiting accurate, consistent, and repeated measurement of forest carbon pools in cities. This study aims to evaluate the uncertainties of forest carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…For example, Simard et al [71] found that the mean tree height was highly related to the aboveground biomass in Everglades National Park. Scale is a crucial issue of the remote-sensing data; the resolution of optical data and the density of LiDAR point cloud have a strong effect on the forest biomass [74,75]. We will explore the effect of remote sensing data with different scales on biomass estimation accuracy in the future.…”
Section: Importance Of Predictive Factors For Model Performancementioning
confidence: 99%
“…For example, Simard et al [71] found that the mean tree height was highly related to the aboveground biomass in Everglades National Park. Scale is a crucial issue of the remote-sensing data; the resolution of optical data and the density of LiDAR point cloud have a strong effect on the forest biomass [74,75]. We will explore the effect of remote sensing data with different scales on biomass estimation accuracy in the future.…”
Section: Importance Of Predictive Factors For Model Performancementioning
confidence: 99%
“…Moreover, as a carbon sink, forest dynamics are closely related to the global carbon cycle and climate changes [2][3][4]. Canopy height is an important forest structure parameter for understanding the forest ecosystem, and has been used to estimate forest aboveground biomass and therefore model the global carbon stock and carbon dynamics [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The spatial variation in aboveground carbon density that we estimated across the central six districts of Beijing emphasized the importance of quantifying carbon stocks using fine‐resolution data. Fragmented urban development often leads to small green patches and isolated trees, and therefore, fine‐spatial resolution remote sensing data used in this study is particularly beneficial to illustrate the spatial variation in carbon storage (Chen et al, ; Mitchell et al, ). Due to the mixed‐pixel problem, each pixel is represented by the predominant land cover, and thus, maps from medium‐resolution remote sensing data such as Landsat could not capture the finely grained green spaces in urbanized areas (Davies et al, ; Raciti et al, ).…”
Section: Discussionmentioning
confidence: 99%